2021
DOI: 10.21037/atm-20-6797
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus accelerates the progression of osteoarthritis in streptozotocin-induced diabetic mice by deteriorating bone microarchitecture, bone mineral composition, and bone strength of subchondral bone

Abstract: Background: The purpose of this study was to develop an optimal diabetes-osteoarthritis (DM-OA) mouse model to validate that diabetes aggravates osteoarthritis (OA) and to evaluate the microarchitecture, chemical composition, and biomechanical properties of subchondral bone (SB) as a consequence of the DM-OAinduced damage induced.Methods: Mice were randomly divided into three groups: DM-OA group, OA group, and sham group.Blood glucose levels, body weight, and food intake of all animals were recorded. Serum cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Chen et al (2017) reported that subchondral bone remodelling led to deteriorated microstructure and strength, which in turn aggravated cartilage degradation in type 2 diabetes patients. In a mouse model, Wang et al (2021) also found that diabetes mellitus accelerates the progression of osteoarthritis in streptozotocin-induced diabetic mice by deteriorating subchondral bone microarchitecture. Using a mouse model with spontaneously hypertensive heart failure and obesity, Deng et al (2018) evaluated the contribution of metabolic syndrome to OA development, which exhibited knee joints with severe loss of the entire thickness of the cartilage A conceptual model of OA including pathogenesis, symptoms, risk factors and treatments.…”
Section: Metabolic Disordersmentioning
confidence: 84%
“…Chen et al (2017) reported that subchondral bone remodelling led to deteriorated microstructure and strength, which in turn aggravated cartilage degradation in type 2 diabetes patients. In a mouse model, Wang et al (2021) also found that diabetes mellitus accelerates the progression of osteoarthritis in streptozotocin-induced diabetic mice by deteriorating subchondral bone microarchitecture. Using a mouse model with spontaneously hypertensive heart failure and obesity, Deng et al (2018) evaluated the contribution of metabolic syndrome to OA development, which exhibited knee joints with severe loss of the entire thickness of the cartilage A conceptual model of OA including pathogenesis, symptoms, risk factors and treatments.…”
Section: Metabolic Disordersmentioning
confidence: 84%
“…The histological severity of OA was also remarkably higher in the diabetic group compared to the control group of mice. A diabetic microenvironment facilitates the development of OA by promoting accelerated synthesis and accumulation of AGEs, further increasing the oxidative burden by impairing healing and elasticity [ 6 ] (Figure 2 ). A study conducted by Dubey et al concluded that the increased glycation products in diabetic mice increasingly induce matrix metalloproteinase expression as well as reduce chondrocytes-specific protein expressions such as SOX9, COl 2, and aggrecan [ 3 ].…”
Section: Reviewmentioning
confidence: 99%
“…The US Third National Health and Nutrition Examination Survey (NHANES III) recently performed a cross-sectional study, which demonstrated a higher prevalence of DM in those with OA as compared to the general population [ 4 ]. Furthermore, it was reported that DM plays a unique role of its own in the progression and pathogenesis of OA [ 4 , 6 ]. Even hyperglycemia alone was reported to be associated with a separate mechanism on the pathogenesis and advancement of OA through the accumulation of advanced glycation end products (AGEs), oxidative stress, and dysregulation of articular cartilage metabolism [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) and osteoporosis are major public health problems in the aging population affecting people all over the world and are of serious health and financial concern ( 1 ). DM can cause great harm to the human body, among which chronic complications of skeletal system have a high rate of death and disability, which can cause long-term bone pain and lead to diabetic osteoporosis ( 2 ).…”
Section: Introductionmentioning
confidence: 99%